POTENSI VEGETASI PAKAN LUTUNG JAWA (Tracypithecus auratus) DI TAMAN WISATA ALAM PANANJUNG PANGANDARAN - Eghi Ramdhani (Wanamukti: Jurnal Penelitian Kehutanan, 2021)
Javan langurs are arboreal and have food preference form of leaves, fruit, and flowers, so very dependent on the vegetation in the forest. The object of research is to know the importent value indexand potential of Javan langurs’s food vegetation. The method of research by systemically structured multiplated grid method. The potential of Javan langur’s food vegetation are 30 species which 23 species of tree, 18 species of seeds, 18 species of saplings, and 11 species of poles. Status of food vegetation divided to 3 availability status are safe, unsafe, and very unsafe. There are 8 species safe,  12 species unsafe, and 10 species very unsafe.